The Evolution of Chinese Outward Foreign Direct Investment Policy - Młody, Michał (Studia Oeconomica Posnaniensia, 2013)
The aim of this article is to summarize the policy of foreign direct investment by China. Deep reforms relating to the adjustment of its FDI strategy to the development model of the Chinese economy were implemented after the year 2000. The factors that have played a particularly important role in creating the upward trend of Chinese FDI include the establishment of institutions responsible for investment financing, numerous bilateral economic agreements with countries all over the world, and introducing a support strategy for overseas investments. The current investment policy has proved to be successful but further reforms will be required in the near future.